2006
DOI: 10.1016/j.gene.2005.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome computational comparative genomics: A fruitful approach for ascertaining Alu insertion polymorphisms

Abstract: Alu elements are the most active and predominant type of short interspersed elements (SINEs) in the human genome. Recently inserted polymorphic (for presence/absence) Alu elements contribute to genome diversity among different human populations, and they are useful genetic markers for population genetic studies. The objective of this study is to identify polymorphic Alu insertions through an in silico comparative genomics approach and to analyze their distribution pattern throughout the human genome. By comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
69
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 51 publications
7
69
0
Order By: Relevance
“…The first of such active groups are L1 elements, the only active autonomous retrotransposons in the human genome, which are also responsible for the mobilization of nonautonomous retrotransposons [Boissinot et al, 2000[Boissinot et al, , 2004Brouha et al, 2003;Dewannieux et al, 2003]. Among the active nonautonomous groups are Alu elements and SVA elements, a composite type of retrotransposon formed of SINE-R, VNTR, and Alu [Boeke, 1997;Boeke and Chapman, 1991;Deininger and Batzer, 2002;Dewannieux et al, 2003;Ostertag et al, 2000Ostertag et al, , 2002Ostertag et al, , 2003Sassaman et al, 1997;Shen et al, 1994;Wang et al, 2005;Wang et al, 2006]. Many of the insertions derived from these active retrotransposons occurred so recently that they are polymorphic with respect to the presence or absence of the insertion in different human populations, families, or even individuals [Batzer et al, 1994;Deininger, 1991, 2002;Boissinot et al, 2000Boissinot et al, , 2004Badge et al, 2003;Bamshad et al, 2003;Myers et al, 2002;Perna et al, 1992;Sheen et al, 2000;Watkins et al, 2001Watkins et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of such active groups are L1 elements, the only active autonomous retrotransposons in the human genome, which are also responsible for the mobilization of nonautonomous retrotransposons [Boissinot et al, 2000[Boissinot et al, , 2004Brouha et al, 2003;Dewannieux et al, 2003]. Among the active nonautonomous groups are Alu elements and SVA elements, a composite type of retrotransposon formed of SINE-R, VNTR, and Alu [Boeke, 1997;Boeke and Chapman, 1991;Deininger and Batzer, 2002;Dewannieux et al, 2003;Ostertag et al, 2000Ostertag et al, , 2002Ostertag et al, , 2003Sassaman et al, 1997;Shen et al, 1994;Wang et al, 2005;Wang et al, 2006]. Many of the insertions derived from these active retrotransposons occurred so recently that they are polymorphic with respect to the presence or absence of the insertion in different human populations, families, or even individuals [Batzer et al, 1994;Deininger, 1991, 2002;Boissinot et al, 2000Boissinot et al, , 2004Badge et al, 2003;Bamshad et al, 2003;Myers et al, 2002;Perna et al, 1992;Sheen et al, 2000;Watkins et al, 2001Watkins et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 505 polymorphic Alu, 65 L1, and 39 SVA elements were recovered by comparing the trace sequences derived from different library sources [Bennett et al, 2004]. By comparing the two versions of the human genome sequences (public vs. Celera www.celera.com), we have recently identified over 800 polymorphic Alu elements and 150 L1 elements [Wang et al, 2006;authors' unpublished data].…”
Section: Introductionmentioning
confidence: 99%
“…Subsets of the Y subfamilies are the only known Alu elements currently active in the human genome, with variants of the Y, Ya, and Yb lineages currently dominating activity (Deininger and Batzer 1999;Hedges et al 2004;Mills et al 2007;Belancio et al 2008). There are ;900,000 older subfamily elements in the genome, predominately variants of the Alu S and J (Wang et al 2006), and yet no de novo disease-associated insertions of these older elements have been found (Belancio et al 2008).…”
mentioning
confidence: 99%
“…There are at least 15 examples of Ya5 elements that have recently inserted causing disease (Belancio et al 2008), despite there being only 3000 copies in the genome (Wang et al 2006). In contrast, the older subfamilies have a 300-fold greater copy number than Ya5 while having no detectable amplification rate, suggesting that there must be at least a 4500-fold enrichment in activity per Ya5 copy relative to the old Alu subfamily members.…”
mentioning
confidence: 99%
“…Second, many RE insertions were predicted by computational screening, and their polymorphism was not confirmed by subsequent experimental studies. 11,24 Consequently, the selection of Alu insertions required some additional studies to meet the criteria indicated in 'Materials and methods.' At the first computational stage we selected 31 autosomal loci: 18 on chromosomes from 1 to 9 (2 per chromosome) and 13 each on 1 of the remaining human chromosomes (from 10 to 22).…”
Section: Resultsmentioning
confidence: 99%